Kitab Ta'limul Muta'allim as a Counter-Culture Medium for the Moral Crisis of Adolescents - Innayatus Sholihah Al-Chanin; Duwi Habsari Mutamimah; Muhammad Fahmi Maulana (Jurnal Paradigma, 2026)
The moral crisis of adolescents characterized by declining manners, enthusiasm for learning, and social concern has become a serious challenge in Islamic education. This study aims to examine the role of the book Ta'limul Muta'allim as a counter-culture medium to the symptoms of moral decadence among the students of the MA Ma'arif Pacitan Dormitory. This study uses a qualitative approach with a contextual study method. Data collection techniques include observation, in-depth interviews, and documentation. The results of the study show that the book of Ta'limul Muta'allim plays an important role in shaping the character of students through the internalization of the values of manners, responsibility, and spirituality. These values are instilled through regular recitation, worship habits, and integration in madrasah culture. Its role as a medium of character education as well as a counter-culture tool has proven to be effective in responding to adolescent moral crises, especially through strengthening teacher examples, a culture of discipline, and support from the family environment. These findings affirm the importance of preserving and strengthening the tradition of classical book education as the foundation for the formation of adolescent characters that are adaptive to the challenges of the times and remain rooted in Islamic values.